Ultrasound-targeted microbubble technology facilitates SAHH gene delivery to treat diabetic cardiomyopathy by activating AMPK pathway - Xiaohui Guo; Kegong Chen; Lin Ji; Shanjie Wang; Xiangmei Ye; Liang Xu; Leiguang Feng (iScience, 2024)
Summary: Diabetic cardiomyopathy (DCM) is a cardiovascular complication with no known cure. In this study, we evaluated the combination of ultrasound-targeted microbubble destruction (UTMD) and cationic microbubbles (CMBs) for cardiac S-adenosyl homocysteine hydrolase (SAHH) gene transfection as potential DCM therapy. Models of high glucose/fat (HG/HF)-induced H9C2 cells and streptozotocin-induced DCM rats were established. Ultrasound-mediated SAHH delivery using CMBs was a safe and noninvasive approach for spatially localized drug administration both in vitro and in vivo. Notably, SAHH overexpression increased cell viability and antioxidative stress and inhibited apoptosis of HG/HF-induced H9C2 cells. Likewise, UTMD-mediated SAHH delivery attenuated apoptosis, oxidative stress, cardiac fibrosis, and myocardial dysfunction in DCM rats. Activation of the AMPK/FOXO3/SIRT3 signaling pathway may be a key mechanism mediating the role of SAHH in regulating myocardial injury. Thus, UTMD-mediated SAHH transfection may be an important advancement in cardiac gene therapy for restoring ventricular function after DCM.